The human side of enterprise - McGregor, Douglas 1906-1964 (McGraw-Hill, 1960)
The text deals with policies and practices in the management of human resources in business and industrial organization, examining them in the light of current social science knowledge about human nature and behavior. Two important suppositions form the basis of this material. Theory X: the assumptions upon which traditional organizations are based and which appear inadequate for the full utilization of human potentialities. Theory Y: the assumptions consistent with current research knowledge which could lead to higher motivation and greater realization of both individual and organizational goals. The implications of Theory Y in regard to the administration of salaries and promotions, performance appraisal, staff-line relationships, participation, leadership, management development, and the managerial team are discussed.
Keywords: Administracao De Pessoal; Management; Personnel - Direction; Arbeitsbedingungen; Betriebsführung; Forschung; Wissenschaftlich-Technischer Fortschritt; Personnel Management; Personnel management; Mitbestimmung; Unternehmensleitung; Motivation; Führung; USA